PEMANFAATAN WEBSITE CIKAKAK ACTIVE LEARNING SEBAGAI SARANA BELAJAR DALAM PEMBELAJARAN SEJARAH BERBASIS DARING (STUDI DESKRIPTIF KUALITATIF DI KELAS XI SMA NEGERI 1 CIKAKAK) - Syifa Senja Sabilillah, - (2022)
This research is motivated by the use of the Cikakak active learning website as a learning tool in online-based history learning in class XI of SMA Negeri 1 Cikakak. The purpose of this research is to describe the implementation of learning by utilizing the Cikakak active learning website which is carried out as a learning tool between teachers and students in online-based history learning during the covid-19 pandemic. The method used in this research is a qualitative descriptive study. The findings of this study indicate that (1) the school and teachers have made efforts to choose e-learning that suits the needs of students in carrying out online-based history learning, namely by utilizing the Cikakak active learning website as a learning tool (2) Utilizing the features that on the Cikakak active learning website, it is quite well optimized by both teachers and students (3) In the implementation of online-based history learning using the Cikakak active learning website, students and teachers encounter obstacles such as learning planning by teachers who cannot be maximized as well as the absence the learning video feature on the Cikakak active learning website, this causes teachers to not be able to control directly and there are restrictions on student assignment files by the teacher. (4) Efforts made include teacher, embed YouTube links in LKPD, teachers creating WhatsApp groups with parents of students and teachers using supporting e-learning, namely google classroom. Keywords: Cikakak Active Learning Website, History Learning, Learning Facilities